2019
DOI: 10.1177/0886260519868197
|View full text |Cite
|
Sign up to set email alerts
|

#MeToo and Google Inquiries Into Sexual Violence: A Hashtag Campaign Can Sustain Information Seeking

Abstract: The #MeToo Movement has brought new attention to sexual harassment and assault. While the movement originates with activist Tarana Burke, actor Alyssa Milano used the phrase on Twitter in October 2017 in response to multiple sexual harassment allegations against Hollywood producer Harvey Weinstein. Within 24 hours, 53,000 people tweeted comments and/or shared personal experiences of sexual violence. The study objective was to measure how information seeking via Google searches for sexual harassment and assault… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Sexual harassment is one of the forms of sexual violence that has traditionally been most studied [13]. This interest has been boosted in recent years motivated, in part, by the media impact and social repercussions of specific acts, such as the accounts of sexual harassment given by victims themselves arising from viral phenomena such as #MeToo [14,15].…”
Section: Of 17mentioning
confidence: 99%
“…Sexual harassment is one of the forms of sexual violence that has traditionally been most studied [13]. This interest has been boosted in recent years motivated, in part, by the media impact and social repercussions of specific acts, such as the accounts of sexual harassment given by victims themselves arising from viral phenomena such as #MeToo [14,15].…”
Section: Of 17mentioning
confidence: 99%
“…• #MeToo (Bogen et al, 2019;Hosterman et al, 2018;Jackson et al, 2019;Kaufman et al, 2019;Lindgren, 2019;Mendes, Ringrose, & Kel ler, 2018;Mendes & Ringrose, 2019;Suk et al, 2019); • #YesAllWomen (Barker Plummer & Barker Plummer, 2017;Rodino-Colocino, 2014;Thrift, 2014); and • #WhyIStayed (Clark, 2016;Weathers et al, 2016).…”
Section: State Of Research On Youtube Videosmentioning
confidence: 99%
“…There is some empirical evidence that #MeToo has had an impact on cultural awareness of sexual assault. One longitudinal analysis of Google search trends indicated #MeToo sparked information seeking on sexual assault and sexual harassment, and this trend was sustained beyond peaks associated with public accusations against high-profile figures (Kaufman et al, 2021). Findings from another longitudinal study revealed that dismissal of sexual assault allegations (i.e., expressing the belief that the increasing number of reports of sexual assault are due to false allegations or that women make allegations to harm men) decreased among both women and men after the popularization of #MeToo (Szekeres et al, 2020).…”
Section: Hashtag Feminism and Sexual Consent In A Culture Of Postfeminist Contradictionsmentioning
confidence: 99%